Upaya Guru Dalam Meningkatkan Pemahaman Aswaja Siswa Melalui Ekstrakurikuler Kajian Aswaja di SMA - Fadila, Nurul; Muliatul Maghfiroh (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Students’ understanding of Ahlussunnah wal Jamaah (Aswaja) values at the senior high school level continues to face challenges, particularly in internalizing the principles of religious moderation in daily life. This study aims to analyze the implementation of the Aswaja extracurricular study program as a strategy employed by Islamic Religious Education (PAI) teachers to enhance students’ understanding and moderate attitudes. The research applied a descriptive qualitative approach, with data collected through observation, structured interviews, and documentation. Informants consisted of PAI teachers, the school principal, and selected students chosen purposively. Data were analyzed through the stages of data reduction, data display, and conclusion drawing, with triangulation techniques employed to ensure validity. The findings reveal that regularly conducted and interactive Aswaja study activities effectively strengthen students’ understanding of tawassuth (moderation), tawazun (balance), and tasamuh (tolerance). Beyond improving cognitive aspects, the program also fosters more open-minded, wise, and tolerant attitudes in responding to differences, thereby contributing to the reinforcement of religious character and the practice of religious moderation within the school environment